PENGARUH ULAMA DAN FATWA MUI TENTANG PENGHARAMAN BUNGA TERHADAP MINAT MASYARAKAT DALAM MEMILIH BANK SYARIAH DI KOTA BEKASI - Agus Sujarwanto (Asosiasi Dosen Muda Indonesia, 2023)
The fatwa of the Indonesian Ulema Council (MUI) regarding the prohibition of usury on 24 January 2004 did receive various responses in society, some took it seriously and used sharia banking services, some responded casually. The MUI fatwa is also suspected of being a driving force for Islamic banks. The purpose of this study was to find the effect of the issuance of the MUI Fatwa regarding the prohibition of usury on people's interest in saving at Islamic or conventional banks in Bekasi City. So that it will be known how much the people's interest in saving and people's preferences in choosing a bank to serve their banking transaction needs. The research results obtained are that the MUI Fatwa significantly affects people's interest in saving at Islamic banks in Bekasi with a significance level of 0.000. This indicates that Ulama still play a major role in providing input in the life of the ummah. Other technical factors such as ATM networks, location and access to Islamic bank offices, saving safety and self-identity of savers also have a major influence in determining people's choices of choosing Islamic banks for their banking services with a significance level of 0.000.